Stochastic dynamics as a limit of Hamiltonian dynamics of hard spheres - Lampis, M.; Petrina, D.Ya.; Petrina, К.D. (Український математичний журнал, 1999)
We consider the stochastic dynamics that is the Boltzmann-Grad limit of the Hamiltonian dynamics of a system of hard spheres. A new concept of averages over states of stochastic systems is introduced, in which the contribution of the hypersurfaces on which stochastic point particles interact is taken into account. We give a rigorous derivation of the infinitesimal operators of the semigroups of evolution operators.